Fabry disease: what the cardiologist should consider in non-cardiac screening, diagnosis, and management—narrative review - Regenbogen, Claudia (Cardiovasc Diagn Ther, 2021)
Fabry disease (FD) is a rare X chromosomally transmitted lysosomal storage disorders with an absence or deficiency of the enzyme alpha-galactosidase. The deposition of globotriaosylceramide (Gb3) may cause damage to all organs, particularly brain, heart and kidney. While acroparaesthesia, hypo- or anhydrosis and diarrhoea are the main symptoms in childhood, cardiac involvement with left ventricular hypertrophy (LVH), renal insufficiency, diffuse pain attacks and apoplexy are the main symptoms in adulthood. Regular examinations are necessary to record organ involvement and its progression. A major challenge is therefore to make a diagnosis at an early disease stage. This is the only way that treatment can be started if there is an indication. If FD is suspected, alpha-galactosidase should be tested in male patients and genetic testing should be performed in females to confirm the diagnosis. Since 2001, enzyme replacement therapy (ERT) has been available as a causal therapy. In 2016, chaperone therapy with the drug Migalastat was approved in the European Union, which leads to stabilisation of the defective alpha-galactosidase. Studies on gene therapy to cure FD in phase I/II. This review summarizes which patient should be screened, how to confirm the diagnosis and which examinations should be performed in FD patients during the course of the disease.